The significance of writing in the digital university environment - Rossette García, Javier (2025)
Developed using a documentary technique, this manuscript aim to present the arguments of the scientific community on the communicative act of writing and its global transcendence when it is disseminated through electronic devices in digital format. This leads to the presentation of positions for and against this phenomenon, where the analysis emphasizes both the opinions in favor of manual writing (analogue text) and those in favor of electronic writing (digitized text). Teachers have to notice the role that new learning environments play, know how to use them and create an axiological awareness in students, about the importance of the normative use of the language that, under any circumstance or context, carries implicit historical-social value.